Toxic Masculinity di TikTok - Kartika, Kartini; Iqbal, Muhammad (Indonesian Journal Publisher, 2023)
This research see the social media that is a free place to express becomes the place which full of boundaries for men because of the demands to be a masculine men and to be accepted in society. This research is aimed to perceive the phenomenon of toxic masculinity in TikTok, and to discover the effects and the person who does the toxic masculinity. This research used netnography method with data analysis techniques through Atlas.ti and be strengthened by social construction of mass media by Peter L. Berger and Thomas Luckmann. This research was conducted by research dislocation in TikTok especially in hastag #toxicmasculinity. The results of this research are quite a lot of people who realize about the negative impact of toxic masculinity that can be seen by some related education contents. Lots of netizens who commented in those contents confessed that they got toxic masculinity directly and in cyber space by family, teachers, and friends. The results of content analysis also showed that the victims feel anxious, stress, and forced to run the male role, thus need to consult to psychologist and psychiatrist as the impact of toxic masculinity.